Pemberdayaan Jabatan Fungsional Analis Sumber Daya Manusia Aparatur dalam Menunjang Pengelolaan ASN di Badan Kepegawaian Daerah (BKD) Provinsi Banten - Dharmawan, Awan; Budiati, Ayuning; Rosidin, Angga (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2025)
This study aims to determine how the development of human resources for the apparatus in the Regional Personnel Agency of Banten Province through the Empowerment of Functional Positions of the HR Apparatus Analyst. In this study, the analysis used was the Human Resource Development Theory Approach with the dimension indicator of employee empowerment related to the title and used a descriptive qualitative approach Observations were made by conducting the interview method on 4 informants who knew the problem. From the results of observations made related to the existing dimension indicators, namely: Dimensions of Ability; Smoothness Dimension; Consulting Dimension; Cooperation Dimensions; Guiding Dimensions; The Supporting Dimensions all show that the Development of Apparatus Human Resources through the Empowerment of Functional Positions of Apparatus Human Resources Analysts at the Regional Personnel Agency (BKD) of Banten Province, has been carried out optimally and is expected to facilitate the main tasks and organizational functions.